2021
DOI: 10.1002/hep4.1683
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Protects Against Acetaminophen‐Induced Hepatotoxicity Mainly by Activating the Carbohydrate‐Response Element‐Binding Protein α–Fibroblast Growth Factor 21 Axis in Mice

Abstract: Acetaminophen (N‐acetyl‐para‐aminophenol [APAP]) overdose is the most common cause of drug‐induced liver injury in the Western world and has limited therapeutic options. As an important dietary component intake, fructose is mainly metabolized in liver, but its impact on APAP‐induced liver injury is not well established. We aimed to examine whether fructose supplementation could protect against APAP‐induced hepatotoxicity and to determine potential fructose‐sensitive intracellular mediators. We found that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Even though acute knockdown of liver Chrebpα using adenoviral transduction in db/db mice results in improved insulin sensitivity, glucose metabolism, and liver steatosis [ 37 ], the pathogenic role of hepatocyte ChREBP⍺ in diet-induced MAFLD/MASH remains unclear. To examine how hepatocyte Chrebp⍺ deficiency in adult mice impacts the onset and progression of this disease, we took advantage of AAV to generate adult-onset hepatocyte-specific Chrebp⍺ knockout ( Chrebp⍺-LKO ) mice [ 56 ]. This approach allowed us to bypass any developmental defects due to the loss of hepatocyte ChREBP⍺.…”
Section: Resultsmentioning
confidence: 99%
“…Even though acute knockdown of liver Chrebpα using adenoviral transduction in db/db mice results in improved insulin sensitivity, glucose metabolism, and liver steatosis [ 37 ], the pathogenic role of hepatocyte ChREBP⍺ in diet-induced MAFLD/MASH remains unclear. To examine how hepatocyte Chrebp⍺ deficiency in adult mice impacts the onset and progression of this disease, we took advantage of AAV to generate adult-onset hepatocyte-specific Chrebp⍺ knockout ( Chrebp⍺-LKO ) mice [ 56 ]. This approach allowed us to bypass any developmental defects due to the loss of hepatocyte ChREBP⍺.…”
Section: Resultsmentioning
confidence: 99%
“…We further revealed that prompt fructose intake after APAP overdose could significantly mitigate liver damage through the activation of the ChREBP-FGF21 axis [53] . Based on literature and our report [52,53] , we propose that fructose could be utilized as a novel detoxification agent for drug-induced liver damage.…”
Section: Fructose Protection Against Apap Toxicity Via the Chrebp-fgf...mentioning
confidence: 97%
“…The mean fructose consumption in the United States is 54.7g/day, with the primary intake being from sugar-sweetened beverages [50] . Although fructose intake can promote de novo lipogenesis and cause insulin resistance, a prelude to diabetes, non-alcoholic fatty liver disease (NAFLD), and obesity, recent studies have highlighted fructose as a potential antidote against APAP-induced hepatotoxicity [51,52] . Our own study also found that fructose ingestion could ameliorate APAP-induced hepatotoxicity.…”
Section: Fructose Protection Against Apap Toxicity Via the Chrebp-fgf...mentioning
confidence: 99%
“…FGF21 forms a stable FGF21/KLB/FGFR complex via β-Klotho (KLB) and FGF receptor (FGFR) to activate downstream related signaling molecules, exerting biological effects and fulfilling corresponding specific functions. The binding of KLB to FGFR4 induces apoptosis and inhibits tumor cell proliferation[ 59 , 60 ]. As the concentration of FGF21 increases, KLB mRNA expression increases, and KLB protein content also increases in a consistent manner.…”
Section: Mitokines-mediated Immune Regulation In Hcc Nucleus-derived ...mentioning
confidence: 99%